2008
DOI: 10.1111/j.1537-2995.2008.01776.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy in reducing potassium load in irradiated red cell bags with a potassium adsorption filter

Abstract: This study has shown a high efficacy in reducing potassium load in irradiated RBC bags with the use of the PAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
3
21
0
1
Order By: Relevance
“…In other words, to maintain electrical neutrality, the number of Na + ions released from the SPS resin is identical to the number of K + , Li + , or H + ions adsorbed by the SPS resin, while two Na + ions are released following adsorption of Mg 2+ or Ca 2+ , and three Na + ions are released following adsorption of Al 3+ . The three earlier studies using this filter showed that the mean reduction in the supernatant K + concentration after a single pass of the stored RBC units was more than 90%, but not 100% . Yamada et al.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In other words, to maintain electrical neutrality, the number of Na + ions released from the SPS resin is identical to the number of K + , Li + , or H + ions adsorbed by the SPS resin, while two Na + ions are released following adsorption of Mg 2+ or Ca 2+ , and three Na + ions are released following adsorption of Al 3+ . The three earlier studies using this filter showed that the mean reduction in the supernatant K + concentration after a single pass of the stored RBC units was more than 90%, but not 100% . Yamada et al.…”
Section: Discussionmentioning
confidence: 95%
“…Cid et al. reported that the K + concentration decreased from 60.6 to 3.4 mEq/L (mean reduction of 94%) in the supernatant of stored irradiated RBC bags after a single filtration. Yamada et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…190, 195, 196, 197, 198, 199, 200, 201, 202, 203, 204, 205, 206, 207 Transmission of infections, although rare, is a major concern and this risk varies between countries (Table 6). 208, 209, 210, 211 These complications are reviewed extensively elsewhere.…”
Section: Rationalementioning
confidence: 99%
“…When blood products with increased potassium concentrations are administered to patients with renal dysfunctions, there is a high risk of causing hyperkalemia. In these cases, a filter (KPF-4, Kawasumi Laboratories, Tokyo, Japan) to adsorb the potassium in the red cell bags is useful [1,2]. It has been reported that the filter is effective for use during surgery as large volume blood transfusions are required [3,4], but it is also useful to patients of renal dysfunctions.…”
Section: To the Editormentioning
confidence: 99%